Providing Policy Makers with Timely Advice : The Timeliness-Rigor Trade-off - Bell, Clive; Squire, Lyn (World Bank, Washington, DC, 2016)
Policy makers bemoan the lack of research findings to guide urgent decisions, whereas researchers' professional code puts rigor first. This article argues that provisional assessments, produced early in the research cycle, can bridge the gap. Numerous case studies point to the importance of early interaction with policy makers and the delivery of brief, policy-focused papers; but preliminary analyses may be flawed and so increase the chances of a wrong decision. This article demonstrates analytically that a preliminary assessment, supported by the offer of more refined research, provides an option that is superior, on average, to the current practice of submitting a final report at the end of the research cycle. Where practical implementation is concerned, it calls for donor-funded subsidies to promote the use of provisional assessments and for a rapid, independent, professional review process to ensure their quality. While the research-policy exchange in developing countries is a complex, context-specific phenomenon, the proposal offered here holds out some promise of improving decisions in the public sphere under a wide range of circumstances.